Impact of Coexistence Phenotype Between Staphylococcus aureus and Pseudomonas aeruginosa Isolates on Clinical Outcomes Among Cystic Fibrosis Patients - Briaud, Paul; Bastien, Sylvère; Camus, Laura; Boyadjian, Marie; Reix, Philippe; Mainguy, Catherine; Vandenesch, François; Doléans-Jordheim, Anne; Moreau, Karen (Frontiers in Cellular and Infection Microbiology, 2020)
Staphylococcus aureus (SA) is the major colonizer of the lungs of cystic fibrosis (CF) patients during childhood and adolescence. As patients age, the prevalence of SA decreases and Pseudomonas aeruginosa (PA) becomes the major pathogen infecting adult lungs. Nonetheless, SA remains significant and patients harbouring both SA and PA are frequently found in the worldwide cohort. The overall impact of co-infection remains controversial. Furthermore, co-infecting isolates may compete or coexist. The aim of this study was to analyse if co-infection and the coexistence of SA and PA could lead to worse clinical outcomes. The clinical and bacteriological data of 212 Lyon CF patients were collected retrospectively, and patients were ranked into three groups, SA only (n=112), PA only (n=48) or SA plus PA (n=52). In addition, SA and PA isolates from co-infected patients were tested in vitro to define their interaction profile. Sixty five percent (n=34) of SA/PA pairs coexist. Using univariate and multivariate analysis, we confirm that SA patients have a less severe clinical condition than others, and PA induces a poor outcome independently of the presence of SA. Regarding co-infection, no significant difference in clinical outcomes was observed between patients with coexisting pairs and patients with competitive pairs. However, when compared to SA mono-infected patients, patients with coexisting pair presented higher frequency and length of hospitalizations and more exacerbations. We suggest that coexistence between SA and PA may be an important step in the natural history of lung bacterial colonization within CF patients.